CMV Infection: A Clinical Challenge in Biological Therapy? The Case of Asymptomatic Patients with Persistent Positive Immunoglobulin M Anti-CMV Treated with Secukinumab - Gambardella, Alessio (Psoriasis (Auckl), 2020)
The use of biological therapy is now common practice in the treatment of immune-mediated inflammatory diseases (IMID). Currently, there are no guidelines related to the management of cytomegalovirus (CMV) infections or reactivation during therapy with biological agents. Furthermore, there is a lack of guidance on the management of asymptomatic patients with persistent positive immunoglobulin (Ig)M anti-CMV after an extended period and who have to undergo therapy with biological agents. We report the case of a patient in this situation for whom treatment with biological drugs for psoriasis was indicated. A good clinical response was obtained with secukinumab and maintained during 6 months of follow-up. No infectious disease or reactivation of CMV infection occurred. We suggest some possible guidelines for the management of such cases.